Influence of Brand Image, Perceived Price, and Word-of-Mouth on Purchase Intention of Lunio Design Products - Jessica, Jessica; Hermeindito, Hermeindito; Henryanto, Aria Ganna (International Business Management - Universitas Ciputra, 2024)
The creative industry is an important factor in creative economic activities. This research aims to analyze the influence of brand image, price perception, and word-of-mouth on purchase intentions for Lunio products. This study uses a quantitative approach by distributing questionnaires to respondents to test the effect of the independent variables on the dependent variable. The independent variables used in this research are brand image, price perception, and word-of-mouth, while the dependent variable is purchase intention. The research population is potential client candidates aged 15–16 years, in high school grades 10–12, and attending private high schools in Surabaya. Lunio sampling used a purposive sampling technique with a total sample of 100 people. This study uses the multiple linear regression analysis method. The results show that brand image is an important variable that significantly influences the intention to buy Lunio Design products. The price perception variable also influences purchase intention, though its significance level is lower compared to the other two variables. Word-of-mouth has the strongest impact on purchase intention. In conclusion, these findings underscore the importance of brand image, price perception, and word-of-mouth in shaping consumer purchase intentions.